Do stock market disruptions induced by oil price shocks affect firm-level investment in South Africa? - Kyalo, Priscah (My University, 2021)
Various studies have been carried out to establish the effects of oil price shocks on various macroeconomic variables in South Africa. These have mostly focused on effects related to the cost of production. However, such studies fail to establish the particular oil shock responsible for the effects as well as the secondary effects of oil price shocks. This study examines the effects of decomposed oil price shocks on firm-level investment in South Africa when the shocks are transmitted through the stock market. The oil price shocks were disentangled into oil demand shock, supply shock and risk shock using Ready (2018) model. The generalised method of moments estimation technique was applied to South Africa firms data over the period 2000 to 2019. The investment model was estimated using Tobin’s Q theory, and augmented with alternate variables including the stock market volatility induced by the disentangled oil shocks. The findings indicate that indeed there exists an oil shock pass-through mechanism with the stock market acting as the channel of transmission. The supply shocks are negatively correlated with stock market returns, but their induced volatility is too small to significantly affect firm-level investment. The demand shocks have a positive effect on stock market returns and consequently positive and statistically significant effect on firm-level investment. Risk shocks are negatively correlated with stock market returns and have a negative and significant effect on firm-level investment. The volatility induced by the three oil shocks jointly has a positive and statistically significant effect on firm-level investment. The study revealed that the demand shocks were dominant over the sample period, hence the positive influence on firm-level investment. The results will be useful to market participants to know what to anticipate in the stock market when they are aware of the prevalent oil shock. They will also be useful to firm managers in deciding on proper timing of investment as well as to policy makers
A thesis submitted to the Faculty of Commerce, Law, and Management, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Management in Finance and Investments, 2021
Keywords: Oil; Stock Market; South Africa; Oil price; SDG-8: Decent work and economic growth